HERG potassium channel activation is shifted by phorbol esters via protein kinase A-dependent pathways* - Kiehn, Johann; Karle, Christoph; Thomas, Dierk; Yao, Xiao-Zhou; Brachmann, Johannes; Kübler, Wolfgang (The journal of biological chemistry, 1998)
We investigated the effects of the phorbol ester phorbol 12-myristate 13-acetate (PMA) on the rapid component of the delayed rectifier potassium current, I Kr, in guinea pig cardiomyocytes and found that theI Kr current amplitude was reduced by 20% with 10 nm PMA and 44% with 100 nm PMA. The ether-a-go-go-related gene (HERG) encodesI Kr in human heart. We expressedHERG heterologously in Xenopus oocytes and investigated the effects of PMA on the delayed rectifier potassium current. Upon application of PMA in a concentration of 100 nm, we found a similar reduction of HERG outward current amplitude by 59%. This reduction was due to a shift in the HERG activation curve by 37 mV. The ED50 for the PMA-induced shift was 9.0 nm. The inactive 4α-phorbol 12-myristate 13-acetate (4α-PMA) had no effect. PMA is known to act by stimulating distinct protein kinase cascades. Additional application of the specific protein kinase C inhibitors chelerythrine (10 μm) or bisindolylmaleimide (1 μm) could not attenuate the PMA-induced shift. In contrast, the shift by PMA was reduced significantly when the specific protein kinase A (PKA) inhibitors H89 (50 μm) or KT5720 (2.5 μm) were applied. Forskolin (400 μm), an activator of the adenylate cyclase that results in PKA activation, shifted the HERG activation curve by 14 mV. Moreover the specific protein kinase C activator 1-stearoyl-2-arachidonylglycerol (10 μm) showed no effect. Our data suggest that mainly PKA is mediating the shift of the HERG activation kinetics.
Artikelversion 4. Januar 2021
Gesehen am 15.05.2024